From “Golden Legend” to “Lives of the Saints” - Jakulis, Martynas (Lietuvos istorijos studijos, 2016)
About the thesis of Gita Drungilienė “Catholic hagiography of the Grand Duchy of Lithuania: Reception, dissemination and elements of the saint’s cult in the late 14th – early 17th century” and its defence